2019
DOI: 10.2147/jaa.s193045
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anxiety and Depression in Eosinophilic Esophagitis: A Scoping Review and Recommendations for Future Research</p>

Abstract: Eosinophilic esophagitis (EoE) is a rapidly emerging chronic disease with limited treatments. Impacting both children and adults, EoE and its treatments have the potential to significantly reduce psychological functioning, including increasing anxiety and depression. In this paper, we provide a scoping review of the scientific literature on anxiety and depression in both pediatric and adult patients. We aim to document the current state of research, identify knowledge gaps, recognize unique challenges that EoE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 52 publications
2
34
0
5
Order By: Relevance
“…Mental health has only very recently been investigated in adult patients with EoE. A 2019 scoping review 32 of anxiety and depression in adults with EoE found only 11 studies in adult patients, with 6 of these measuring anxiety via a measure of HRQoL (EoE-QOL-A) vs a psychiatric questionnaire, such as the Hospital Anxiety and Depression Scale (HADS). In the only cross-sectional study before 2019 specifically measuring anxiety via the HADS, 31.1% of 170 patients scored above the clinical cutoff for anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health has only very recently been investigated in adult patients with EoE. A 2019 scoping review 32 of anxiety and depression in adults with EoE found only 11 studies in adult patients, with 6 of these measuring anxiety via a measure of HRQoL (EoE-QOL-A) vs a psychiatric questionnaire, such as the Hospital Anxiety and Depression Scale (HADS). In the only cross-sectional study before 2019 specifically measuring anxiety via the HADS, 31.1% of 170 patients scored above the clinical cutoff for anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Jose et al found that parents of pediatric patients with EoE reported more school avoidance compared to patients without EoE [ 12 ]. Therapy, especially dietary elimination, has been shown to lead to increased worry about embarrassment in social situations [ 13 ]. This study showed that despite the burdens of disease, social functioning remained relatively well-preserved.…”
Section: Discussionmentioning
confidence: 99%
“…This study presents several questions about the quality of life, which should be further investigated. A number of studies have assessed the impact of EoE on specific aspects of physical and psychological functioning such as dysphagia, pain, anxiety, and depression [ 6 , 9 , 13 ]. However, it would be beneficial to investigate other aspects of school and social functioning such as perceptions of support from peers and teachers and adequacy of provisions for the patient at school.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with EGIDs usually report impaired quality of life, due to both their disease and EGID-related therapies [ 32 , 33 , 34 ]. Thus, we have investigated the psychological impact of COVID-19 outbreak in our population.…”
Section: Discussionmentioning
confidence: 99%